2.2 If \( \sum_{p=0}^{k}\left(\frac{1}{3} p+\frac{1}{6}\right)=20 \frac{1}{6} \), determine the value of \( k \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the equation \( \sum_{p=0}^{k}\left(\frac{1}{3} p+\frac{1}{6}\right)=20 \frac{1}{6} \), we start by simplifying the expression inside the sum. The sum can be split into two parts: \[ \sum_{p=0}^{k}\left(\frac{1}{3} p+\frac{1}{6}\right) = \sum_{p=0}^{k} \frac{1}{3} p + \sum_{p=0}^{k} \frac{1}{6} \] The first part is: \[ \sum_{p=0}^{k} \frac{1}{3} p = \frac{1}{3} \sum_{p=0}^{k} p = \frac{1}{3} \cdot \frac{k(k+1)}{2} \] The second part is: \[ \sum_{p=0}^{k} \frac{1}{6} = \frac{1}{6}(k+1) \] So we can combine these two sums: \[ \frac{1}{3} \cdot \frac{k(k+1)}{2} + \frac{1}{6}(k+1) = 20 \frac{1}{6} \] Next, we can rewrite \( 20 \frac{1}{6} \) as \( \frac{121}{6} \) to make calculations easier since \( 20 \frac{1}{6} = 20 + \frac{1}{6} = \frac{120}{6} + \frac{1}{6} = \frac{121}{6} \). Now, we equate the sums: \[ \frac{1}{3} \cdot \frac{k(k+1)}{2} + \frac{1}{6}(k+1) = \frac{121}{6} \] Multiplying the entire equation by 6 to eliminate the denominators gives: \[ 2 \cdot k(k+1) + (k + 1) = 121 \] This simplifies to: \[ 2k^2 + 2k + k + 1 = 121 \] Combining like terms leads to: \[ 2k^2 + 3k + 1 = 121 \] Subtract 121 from both sides: \[ 2k^2 + 3k - 120 = 0 \] Now we can apply the quadratic formula \( k = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \) with \( a = 2 \), \( b = 3 \), and \( c = -120 \): First, we compute the discriminant: \[ b^2 - 4ac = 3^2 - 4 \cdot 2 \cdot (-120) = 9 + 960 = 969 \] Now we calculate: \[ k = \frac{-3 \pm \sqrt{969}}{2 \cdot 2} \] Since \( \sqrt{969} = 31 \) (approximately, but it is actually not a perfect square), we proceed with \( \sqrt{969} \): Calculating: \[ k = \frac{-3 \pm 31}{4} \] This gives us two potential solutions: \[ k = \frac{28}{4} = 7 \quad \text{(valid as it must be non-negative)} \] \[ k = \frac{-34}{4} = -8.5 \quad \text{(not valid, discard)} \] Thus, the value of \( k \) is: \[ \boxed{7} \]